The inescapable context. The arms and letters in the «Royal Commentaries» - Reto Agurto, Alexis (Mercurio Peruano, 2016)
The Incas had no letters, but they were not incult. They inquired about their origins and invented stories which reflected on their existential and religious questions. The lack of letters was not an obstacle to their imperial realization nor prevented the spiritual and political mission of Manco Capac, who set the civilizing impulse of the Incas. The Royal Commentaries with this utopian and renaissance vision of Tahuantinsuyo, also conceal an anthropological interest in portraying a new image of the humanized Inca, equated to any other person althoug not being from the same geographical origin. Inca Garcilaso was late to open discurrions after the conquest, but in time to defend the capability of Indians to learn and decide their own destiny, to provide an image that meets itself the virtues of weapons and letters according to the European model.